Predictors and outcomes of motivation to learn - Wisniewski, Jessica N. (University of Wisconsin--Stout, 2019)
The purpose of the current study was to explore the relationship between variables that influence employee motivation to participate in learning, and their connections to specific behavioral outcomes. The predictor variables in the current study included the Big Five and perceived organizational support (POS). Outcome variables that were studied included: motivation, organizational commitment, and self-efficacy. Autonomy was explored as a mediating variable between the predictor and outcome variables for employee motivation to participate in learning. A survey was shared via social media and completed by a total of 142 respondents. Results indicated that agreeableness, openness to experience, and self-regulation predicted motivation to learn, but POS did not predict motivation to learn. Autonomy did not serve as a mediating variable in any of the predicted relationships. Self-regulation predicted motivation and selfefficacy. Lastly, motivation to learn was a significant predictor of motivation, affective commitment, and self-efficacy.
Keywords: Employee motivation; Organizational commitment; Self-efficacy